Different sources of sulfur in diets of adult cats on the urinary parameters and acid-base balance - Haiku, Doris Pereira; Kessler, Alexandre de Mello; Trevizan, Luciano; Jeremias, Juliana Toloi [UNESP]; Annibale Vendramini, Thiago Henrique; Fernandes Santos, Joao Paulo; Oba, Patricia Massae; Teixeira, Fabio Alves; Brunetto, Marcio Antonio; Carciofi, Aulus Cavalieri [UNESP] (Univ Federal Santa Maria, 2018)
Urolithiasis is a common disorder in the veterinary clinic and is considered as one of the most frequently cause of morbidity. This disorder is closely associated with urinary pH and nutrition plays a key role in the control of this disease, because through dietary manipulation it is possible to modify the urinary pH. Sulfur is considered macroelement with a strong influence on the acid-base status and may be crucial to control urinary pH in cats. The purpose of this study was to evaluate the effects of addition of different sources of sulfur (S) in the diet of cats on the urinary parameters and acid-base balance. Forty-two healthy adult cats were divided into 3 groups, and each group of 14 cats received 7 diets in a complete randomized block design. Calcium sulfate (CaSO4), DL-methionine (DLM) and methionine hydroxy analog (MHA) were added to a control diet in two levels (1.28g S/kg and 2.56g S/kg) to formulate 6 other experimental diets. The acid-base balance was evaluated by hemogasometry in samples of venous blood. The DLM at the highest level and MHA differed of the control diet in relation to urinary pH (P<0.05). Calcium sulfate; although, not differentiated from the control diet, has been shown to alter urinary pH despite its zero electrolyte balance. Apparently, the alkalizing effect of calcium was not sufficient to avoid sulfate acidification of the urine. Treatments showed no alteration of the acid-base balance of the animals and no affect the consumption of the diets.
Keywords: calcium sulfate; felines; methionine; methionine hydroxy analogue; urolithiasis